(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article shows that the systemic-linguistic organization of tourist discourse depends on a number of extralinguistic factors, namely on the psychological characteristics of a person, his mentality, a specific ethnic group, social and cultural type.